The Efficiency and Effectiveness of capital expenditure in the Province of South Sulawesi - Sahade, Sahade (Jurnal Ilmiah Ilmu Administrasi Publik, 2020)
This study aims to describe the efficiency and effectiveness of capital expenditure in the Province of South Sulawesi. To study this problem, ex post facto research is used. The data type uses secondary data for 2009-2013 time brackets. Data collection techniques using study documentation. Based on the results of the study found that the amount of indirect expenditure still dominates the regional expenditure allocation. While indirect spending is consumptive, while direct expenditure tends to be both short-term and long-term investment. Based on the results of the analysis during 2009-2013 which uses the consumption approach rather than the production approach. But this approach produces growth, but it is short-term and volatile. Overall, based on the profile of expenditure allocation, it can be said that the implementation has not been carried out efficiently and effectively. In the future, it is expected that the Regional Government of South Sulawesi Province can increase the allocation of direct expenditure so that there is a balance with indirect spending, so that conditions in the long run are very beneficial because it increases the overall welfare of the community quickly and sustainably.